Agricultura familiar e gestão de custos: um estudo de caso na região do semi-árido baiano - Alves, Carmen de Almeida (2010)
This study aimed to learn the accounting controls and strategies for production planning undertaken by the farmers cooperative of Family Agriculture Cooperative of Canudos Uauá and Curaçá - COOPERCUC - situated in the semi-arid environments. The survey also emphasized the importance of participation by gender and the benefits arising from the programs of public policies in the training of family income. This research was based on the science of agroecology that have as a multidisciplinary scientific approach, knowledge and experiences of the farmers themselves. To foster social participation and the perception of farmers on the importance of the use of accounting control rural family in economic planning, we used an alternative methodology playful, constructivist, participatory and reflective collude with the Science of Agroecology. The survey will serve to reflect the family farmer in its importance in the political and economic region and the country, especially its power to influence government decisions and effective public policies for this segment. Taking as a motivational tool string dynamics for the participatory construction of knowledge that has been proven to promote an educational process by considering the cultural knowledge, social environment in the discussion group on economic management within the unit and how this affects the endogenous development site.